Perbaikan Work Cell XCSPA dengan Metode Lean Six Sigma - Chris Hansen; I Gede Agus Widyadana (Jurnal Titra, 2013)
This study discuss about XCSPA product’s work cell with lean problem WIP after curing process with the maximum location capacity 2640 pieces. Quality issue with main problem contact resistance has resistance value above 25 mΩ, will impact to product function. This study objective is doing improvement to work cell with Lean Six Sigma Method, for improve lean problem and quality issue. In this research, DMAIC is used to solve the problem, however we did not discuss the Improve step. Value Stream Mapping tool used for knowing value added and non-value added process with improvement opportunity. Quality tool using Process Failure Mode & Effect Analysis (PFMEA) for finding cause of problem and potential problem can be happened in XCSPA Work Cell. Reduction of WIP by rearrange WIP quantity between process that will reducing about 85.49% WIP quantity from VSM current state WIP quantity. Quality issue eliminated by change and modify production process. Eliminate quality issue will impact to CNQ reduction for the reject product. Target achievement stated has accomplish that was reduction of PLT from contribution of WIP reducing, otherwise MDR, PRR still can’t be monitored. There’s 26 improvement suggestion, with 11 suggestion done, 7 suggestion in progress, 5 suggestion not yet implemented, 3 suggestion aborted.